Pengaruh Kompetensi, Motivasi Budaya Organisasional Kinerja Dosen Dimediasi Kepuasan Kerja Pada “ MMTC” Yogyakarta - Supardi Supardi (Mahesa Research Center, 2021)
This research is about the influence of competence, motivation and organizational culture on lecturer performance mediated by job satisfaction at